Identifying the Executive Challenges of the New Generation of Hospital Accreditation in Iran - Habibeh Khoshamooz; Mehrdad Goudarzvand chegini; Hamidreza Rezaee Kelidbari (Rāhburdhā-yi Mudīriyyat dar Niẓām-i Salāmat, 2020)
Background: Given that hospitals are one of the pillars of the health system, reforming the health system is not possible without improving the performance of hospitals. Accreditation is a regular assessment of hospitals that emphasizes on continuous quality improvement and patient safety. This study aimed to identify the challenges of the new generation of hospital accreditation using the Three-Branch Model and proposing solutions to improve its effectiveness. Method: This mixed exploratory research was conducted using a targeted sampling method of 20 semi-structured interviews along with a content analysis approach. As a result, an initial model was designed. Later, the initial model was modified using the Delphi technique, which was also approved by experts. In order to test the model, a researcher-made questionnaire was distributed among 384 hospital staff based on Morganchr('39')s table using stratified quota sampling method. Data were analyzed by confirmatory factor analysis using Smart PlS 3 software. Results: After analyzing and combining, the data were categorized under 31 basic codes, 5 concepts, and 3 main categories by Three-branch Model. The main codes included behavioral challenges, structural challenges, and contextual challenges. Conclusion: According to the findings, the main challenge was related to the behavioral category followed by the structural category, which indiates that the current focus is on intra-organizational issues. Therefore, it can be said that the contextual challenges have received less attention.